Innovative Products on the Market of Gastronomic Tourism in Ukraine (on the Example of Cheese Factories of Lviv Region) - Цимбала, Ольга Стефанівна; Дорош, Юлія Степанівна (Київський національний університет імені Тараса Шевченка, 2022)
Purpose. To analyze the current state of development of gastronomic tourism in Lviv region, in particular, the area related to the activities of dairy farms engaged in cheese making and presenting their products and services in the tourist market of the region; to systematize data on key areas of their work, to reflect the specifics of the formation of the tourist offer; describe the main tourist services; cartographically visualize the location of tourist-oriented cheese factories within the region. Method. The study used the method of scientific systematization of information to identify those farms in Lviv region that specialize in cheesemaking and work in parallel in the tourism market; methods of field research and surveys revealed the specifics of individual farms, key areas of their work, problems and prospects for tourism development; with the help of a cartographic method the location of the studied farms within the region is visualized.. Results. The study characterizes the main products produced by the studied farms, and also highlights and systematizes the range of tourist services that the owners of farms and cheese factories offer to their visitors. In particular, all studied farms actively combine farming and tourism activities, but differ in their approaches to farming, the presence or absence of their own farm, and the scale of production. However, everyone is engaged in cheese making, which is the basis of the development of gastronomic tourism. The location of these farms within the region is shown on the map, which allows to visualize the studied farms within the region, as well as the proximity or distance from the main tourist centers of the region. The activities of farms that plan to occupy the niche of tourism-oriented cheese factories in the region are studied. The key problems and prospects for the development of cheese factories in the tourism market of the region are summarized. The scientific novelty of the obtained results consists in the generalization of information about the active cheese factories of the Lviv region, the analysis of their offer on the tourist market and the prospects for further use. The practical significance lies in the systematization of information about the current state of development of cheese factories in the Lviv region. The obtained scientific results can be used in the process of forming tours of Lviv Oblast, as well as in the educational process of training future specialists in the specialty «Tourism». In addition, the findings can be useful for state authorities for the formation and implementation of state and regional programs for the development of tourism, and the formation of strategies for the near future.

Мета. Проаналізувати сучасний стан розвитку гастрономічного туризму Львівщини, зокрема напрямок, що пов’язаний із діяльністю молочних ферм, які займаються сироварінням та презентують свої продукти і послуги на туристичному ринку регіону; здійснити систематизацію даних про ключові напрямки їхньої роботи, відобразити специфіку формування туристичної пропозиції; охарактеризувати основні туристичних послуги; картографічно візуалізувати розміщення туристично-орієнтованих сироварень у межах області. Методика. У дослідженні застосовано метод наукової систематизації інформації для виокремлення тих господарств Львівщини, які спеціалізуються на сироварінні і паралельно працюють на туристичному ринку; методи польових досліджень та опитування дозволили виявити специфіку діяльності окремих господарств, ключові напрямки їхньої роботи, проблеми та перспективи туристичного розвитку; за допомогою картографічного методу візуалізовано розташування досліджуваних господарств в межах області. Результати. У дослідженні охарактеризовано основну продукцію, яку виготовляють досліджувані господарства, а також виділено та систематизовано спектр туристичних послуг, які власники ферм та сироварень пропонують своїм відвідувачам. Зокрема, всі досліджувані господарства активно поєднують фермерську та туристичну діяльність, однак відрізняються своїми підходами до ведення господарства, наявністю чи відсутністю власної ферми, масштабами виготовлення продукції. Однак усі займаються сироварінням, що є основою розвитку гастрономічного туризму. Розташування цих господарств у межах області показано на картосхемі, яка дозволяє візуалізувати досліджувані господарства у межах області, а також близькість чи віддаленість від основних туристичних центрів регіону. Вивчено діяльність фермерських господарств, що планують зайняти нішу туристично-орієнтованих сироварень у регіоні. Узагальнено ключові проблеми та перспективи розвитку сироварень на туристичному ринку області. Наукова новизна отриманих результатів полягає в узагальненні інформації про діючі сироварні Львівщини, аналізі їхньої пропозиції на туристичному ринку та перспективах подальшого використання. Практична значимість полягає в систематизації актуальної інформації про сучасний стан розвитку сироварень Львівської області. Одержані наукові результати можуть бути використані в процесі формування турів Львівщиною, а також в освітньому процесі при підготовці майбутніх фахівців за спеціальністю «Туризм». Крім того, напрацювання можуть бути корисними для органів державної влади для формування і реалізації державних та регіональних програм розвитку туризму, формування стратегій на найближчу перспективу.
Інноваційні продукти на ринку послуг гастрономічного туризму в Україні (на прикладі сироварень Львівської області)
Keywords: інновації; сироварня; фермерське господарство; гастрономічний туризм; Львівщина; innovations cheese factory; tourist-oriented farm; gastronomic tourism; Lviv region